IMPLEMENTATION OF SHARIA ECONOMICS IN SUSTAINABLE DEVELOPMENT: A CASE STUDY OF DEVELOPMENT MANAGEMENT IN BERAU REGENCY - Yuliani, Ma'rifah (Penelitian dan Pengembangan Ilmu, 2025)
This study analyzes the potential of the implementation of sharia economics in supporting sustainable development in Berau Regency, East Kalimantan. Using a descriptive-analytical approach and secondary data from BPS as well as the latest literature (2021-2025), this study identifies opportunities for the integration of sharia economic principles in regional development management. The results of the study show that Berau Regency has significant potential to develop the sharia economy through the halal tourism sector, halal industry, and sharia finance. Recommendations include the development of policy frameworks that support the sharia economic ecosystem and the capacity building of human resources in the field of sharia economics.